2018
DOI: 10.2147/opth.s170789
|View full text |Cite
|
Sign up to set email alerts
|

Coding patterns used by ophthalmologists for hydroxychloroquine retinal toxicity

Abstract: PurposeThe aim of this study was to characterize International Classification of Diseases (ICD-9) coding patterns used by ophthalmologists in clinical practice for hydroxychloroquine (HCQ) retinal toxicity.DesignThis is a retrospective cohort study.SubjectsPatients enrolled in the Kaiser Permanente Southern California health plan who were dispensed HCQ between 2001 and 2014 were included in this study.MethodsPatients’ medical records were electronically searched for the following ICD-9 codes that can be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…For future analysis we also aim to include patient use of hydroxychloroquine, a treatment used for autoimmune conditions and capable of leading to retinal toxicity at higher dose concentrations. However, insurance claim databases at this time do not generally include dosage frequency, and inconsistencies in ICD-9 coding for hydroxychloroquine retinal toxicity have been observed 58. Despite the current limitations in health claim analysis, our analyses provide compelling data on the association between RA and dry AMD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…For future analysis we also aim to include patient use of hydroxychloroquine, a treatment used for autoimmune conditions and capable of leading to retinal toxicity at higher dose concentrations. However, insurance claim databases at this time do not generally include dosage frequency, and inconsistencies in ICD-9 coding for hydroxychloroquine retinal toxicity have been observed 58. Despite the current limitations in health claim analysis, our analyses provide compelling data on the association between RA and dry AMD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The ICD codes used for HCQ retinopathy mostly were 362.10 and 362.55 in the previous literature. [13] However, in the early stage of HCQ retinal toxicity, the macular degeneration was relatively unspecific, thus 362.89 and 362.9 were also included in our study to detect potential HCQ retinopathy. We ruled out patients who were previously diagnosed these retinal disorders, and 5745 patients remained for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Although we did not conduct the equivalent screening manually, in previous work, we were able to use our AI to match a published systematic literature review on inflammatory bowel disease [14], and therefore have already demonstrated that we can generate the equivalent screening using our tool to that obtained with a manual process. [15] incidence of hydroxychloroquine-related retinopathy patients who were treated with recommended dosages of the drug for a mean of 8.7 years 400 2 Mavrikakis et al [15] retinal toxicity was noted during the first 6 years of treatment hydroxychloroquine 526 0 Spinelli et al [16] ophthalmological alterations, confirmed by the ophthalmological examination chloroquine, hydroxychloroquine, or both 845 46 Navajas et al [17] developed retinal toxicity with scotomas in the Amsler grid and Humphrey 10-2 automated perimetry, as well as abnormal multifocal electroretinography 800 mg/day hydroxychloroquine 12 3 Singh et al [18] documented blindness, in all cases attributed to a cause other than hydroxychloroquine-related ocular toxicity long-term hydroxychloroquine 11 0 Chiu et al [19] had hydroxychloroquine toxicity hydroxychloroquine 678 35…”
Section: Rma Process For the Association Of Eye Issues With Hydroxychloroquine Usementioning
confidence: 98%